Information Technology in Health Care 2007 : Proceedings of the 3rd International Conference on Information Technology in Health Care: Socio-technical Approaches - Westbrook, Johanna I (IOS Press, 2013)
Many healthcare ICT innovations fail in practice because of a failure to take into account user needs. User needs should be identified broadly, encompassing different levels of organization of the healthcare system and different stakeholder concerns. Full-scale simulators are starting to be used to help in the design and evaluation of novel biomedical devices and displays. Although promising, simulators have significant technical and operational limitations for this purpose and they do not address important aspects of the sociotechnical systems context in which healthcare ICT will be embedded. This argument is illustrated with a case study in which advanced auditory displays for patient monitoring were successfully evaluated in a full-scale patient simulator, but many further questions remain prior to successful translation to practice.